An Investigation Of The R&D Anomaly In The U.S. And Europe: Implications For Mispricing Theory - Prinsloo, Pierre-Jean (Department of Finance and Tax, 2024)
Belonging in the city of Cape Town is a contested and ambivalent terrain. The past spatial injustices of colonial and apartheid rule have left deep scars and practices embedded in the city. Much has been researched and written about the role of women in land and housing struggles in the Cape. However, there is a gap in the understanding of the interior worlds of black women and how they access resources within for navigating and negotiating belonging in their everyday lives. According to de Certeau's belonging refers to an “everyday ritualized use of space, an appropriation and territorialisation” (and) a “process of transformation of a place, which becomes a space of accumulated attachment and sentiments by means of everyday practices” (de Certeau, 1984: p96). Picking up on this notion of belonging, my research aims to recognize, identify and understand meaning and sense making, humour and the emotional lives of women. The thesis focuses on the lives of three women from one family: each representing a different generation (grandmother, daughter, granddaughter). The thesis explores memoryscapes as that intersection between memory, its tangible aspects such as place, objects and architecture, and that of story. Using narrative enquiry and creative methods of analysis as qualitative research method, the research asks how belonging is negotiated by black women in a postcolonial city. The thesis starts by introducing four strands of literature that inform the research: 1) I engaged with urban studies theory, challenging developmental approaches to postcolonial city formation; Rodaway,2002, Middleton, 2017, Lefebvre, 1996, Jeannotte, 2007, ed. Schindel and Colombo, 2014. 2) I argue that what are missing in the theory are the everyday, ordinary, and interior lives of women. I therefore engaged with feminist scholars such as Hartman, 2019, Butler, 2016, Carby, 2019); 3) I introduce how interiority can enrich literature on belonging Hartman, 2019, Carby, 2019; and 4) I introduce why memory work is crucial to this kind of inquiry; (ed) Field, Meyer, Swanson,2007, Said, 2000, Stoler, 2013, Ricouer, 2004, McKittrick, 2007. The thesis then introduces the qualitative approach to the research, paying particular attention to how narrative forms of inquiry Bochner and Riggs, 2014, Rosenwald and Ochberg, 1992 and visual modes of analysis Elliott and Culhane ed, 2017 and Butler-Kisber, 2010 can enrich urban enquiry. The thesis turns to unpacking the findings through a series of three vignettes entitled ‘I am cheeky you know', ‘umnqusho, amagwinya and tea' and ‘these acts of belonging'. The thesis ends with sharing four key aspects which come to light through the research. The first is that a rich interior life provides a resource for not only coping with life in the city in the everyday, but also strengthens resilience, identity and hence the ability to navigate belonging. The second finding was a set of key strategies deployed by the three women in their navigation of belonging. The third finding is that a process of intersecting story, archival and digital images into a series of collages presented a visual language through which to decode belonging and to make visible the invisible worlds which inform affective relationships, choices and decisions about the city. Finally, it is therefore critical for urban studies to engage more deeply and consistently with the ways in which interiority inform navigation and experiences of belonging in postcolonial cities.